2020
DOI: 10.1007/s40860-020-00109-y
|View full text |Cite
|
Sign up to set email alerts
|

Embodiment matters: toward culture-specific robotized counselling

Abstract: In this paper, we propose adding the traditional Japanese nodding behavior to the repertoire of social movements to be used in the context of humanrobot interaction. Our approach is motivated by the notion that in many cultures, trust-building can be boosted by small body gestures. We discuss the integration of a robot capable of such movements within CRECA, our context-respectful counseling agent. The frequent nodding called "unazuki" in Japan, often accompanying the "un-un" sound (meaning "I agree") of Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Several works showed that ServBots could appear courteous and engaging (IJ dimension: politeness ) through their capacity to dialogue and display identifiable human emotions (Kharub et al 2021 ; Rincon et al 2019 ). ServBots can deliver an empathic speech and voice (James et al 2020 ), understand jokes (Fung et al 2016 ), and display small social behaviors like nodding (Sakurai et al 2020 ) to increase customers' perception of ServBots' social agency, sincerity, and engagement. Servbots can also appear honest and trustful (IJ dimension: respect ) through human-like features (Cominelli et al 2021 ; Roesler et al 2021 ), cute faces (Pinney et al 2022 ), extroverted voice pitch (Niculescu et al 2013 ), and small social behaviors (Sakurai et al 2020 ).…”
Section: Servbots' Capacity To Use Ij During Service Recovery: a Comp...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several works showed that ServBots could appear courteous and engaging (IJ dimension: politeness ) through their capacity to dialogue and display identifiable human emotions (Kharub et al 2021 ; Rincon et al 2019 ). ServBots can deliver an empathic speech and voice (James et al 2020 ), understand jokes (Fung et al 2016 ), and display small social behaviors like nodding (Sakurai et al 2020 ) to increase customers' perception of ServBots' social agency, sincerity, and engagement. Servbots can also appear honest and trustful (IJ dimension: respect ) through human-like features (Cominelli et al 2021 ; Roesler et al 2021 ), cute faces (Pinney et al 2022 ), extroverted voice pitch (Niculescu et al 2013 ), and small social behaviors (Sakurai et al 2020 ).…”
Section: Servbots' Capacity To Use Ij During Service Recovery: a Comp...mentioning
confidence: 99%
“…ServBots can deliver an empathic speech and voice (James et al 2020 ), understand jokes (Fung et al 2016 ), and display small social behaviors like nodding (Sakurai et al 2020 ) to increase customers' perception of ServBots' social agency, sincerity, and engagement. Servbots can also appear honest and trustful (IJ dimension: respect ) through human-like features (Cominelli et al 2021 ; Roesler et al 2021 ), cute faces (Pinney et al 2022 ), extroverted voice pitch (Niculescu et al 2013 ), and small social behaviors (Sakurai et al 2020 ). ServBots' capacity to display emotional expressions also increases customers' perception of trustfulness (Acosta-Mitjans et al 2019 ).…”
Section: Servbots' Capacity To Use Ij During Service Recovery: a Comp...mentioning
confidence: 99%
See 1 more Smart Citation
“…CRECA uses not only ELIZA-style mirroring but also generates its own responses for digging [ 5 ]. Furthermore, it periodically attempts to summarize the clients’ previous utterances considering their emotional impact and chronological order.…”
Section: Vica: Mental Care Counseling Ai Applicationmentioning
confidence: 99%
“… AI counseling agent called VICA (VIsual Counseling Agent) [ 4 ]. Robot (version of) VICA, namely, VICA’s IoT (Internet of Things oriented robot [ 5 ]). These agent systems help mentally distressed or anxious persons by conversation or interchanges.…”
Section: Introductionmentioning
confidence: 99%